Impact of diet and genes on murine autoimmune pancreatitis. Issue 15 (8th July 2020) - Jaster, Robert; Gupta, Yask; Rohde, Sarah; Ehlers, Luise; Nizze, Horst; Vorobyev, Artem; Ludwig, Ralf J.; Ibrahim, Saleh M.
Abstract: The impact of environmental factors, such as diet, and the genetic basis of autoimmune pancreatitis (AIP) are largely unknown. Here, we used an experimental murine AIP model to identify the contribution of diet to AIP development, as well as to fine‐map AIP‐associated genes in outbred mice prone to develop the disease. For this purpose, we fed mice of an autoimmune‐prone intercross line (AIL) three different diets (control, calorie‐reduced and western diet) for 6 months, at which point the mice were genotyped and phenotyped for AIP. Overall, 269 out of 734 mice (36.6%) developed AIP with signs of parenchymal destruction, equally affecting mice of both sexes. AIP prevalence and severity were reduced by approximately 50% in mice held under caloric restriction compared to those fed control or western diet. We identified a quantitative trait locus (QTL) on chromosome 4 to be associated with AIP, which is located within a previously reported QTL. This association does not change when considering diet or sex as an additional variable for the mapping. Using whole‐genome sequences of the AIL founder strains, we resolved this QTL to a single candidate gene, namely Map3k7 . Expression of Map3k7 was largely restricted to islet cells as well as lymphocytes found in the exocrine pancreas of mice with AIP. Our studies suggest a major impact of diet on AIP. Furthermore, we identify Map3k7 as a novel susceptibility gene for experimental AIP. Both findings warrant clinical translation.